Pemberdayaan Ekonomi Kelompok Majelis Taklim Melalui Pelatihan Pembuatan Produk Rumah Tangga sebagai Upaya Ide Bisnis - Dewi, Ika Nurani; Sumarjan, Sumarjan; Primawati, Sri Nopita; Jannah, Husnul; Utami, Septiana Dwi; Atmaja, I Gde Dharma; Jaya, Satriya; Wijaya, Ahmad Ihrom (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Community empowerment is very important, especially for women to have an entrepreneurial spirit to develop a productive economy, so as to improve family welfare. The Majlis Taklim group as a non-formal educational institution in society has great potential and role when it can be empowered optimally. Therefore, the target of this community service activity is the Assyifa Taklim Assembly women group in the Pejeruk Village Environment, Ampenan District, Mataram City. The problem faced by partners is the economic situation of families who are in the middle economy, whereas meeting their daily needs requires increasing spending. By making your own household cleaning soap, you can reduce people's spending on buying household soap, which is quite expensive. The purpose of this activity is to: 1) improve the skills of the Assyifa Taklim Assembly group; and 2) as a home business opportunity for housewives, so as to grow and improve the family economy. Apart from that, marketing opportunities for household soap are wide open, due to the proliferation of laundry businesses in the Pejeruk Village Environment. The methods used to achieve these objectives are: 1) counseling/supplying of materials, this activity is carried out by providing material on how to make dish soap and detergent; 2) training by practicing soap making; and 3) evaluation to measure the absorption of the taklim assembly members on the material presented. This training activity involved all members of the Assyifa Taklim Assembly, totaling 32 people. In the community service activities, raw materials, work procedures, and calculation of production costs for making soap are explained. The results of the training showed the high enthusiasm and activeness of all participants. All of the trainees did well in practicing the manufacture of household products.